Unique and Common Features of Innate-Like Human Vδ2+ γδT Cells and Mucosal-Associated Invariant T Cells - Provine, Nicholas M.; Binder, Benedikt; FitzPatrick, Michael E. B.; Schuch, Anita; Garner, Lucy C.; Williamson, Kate D.; van Wilgenburg, Bonnie; Thimme, Robert; Klenerman, Paul; Hofmann, Maike (Frontiers in Immunology, 2018)
Mucosal-associated invariant T (MAIT) cells are innate-like T cells abundant in humans that can be activated in a TCR-independent manner by inflammatory and anti-viral cytokines. In humans, the capacity for TCR-independent activation is functionally linked to a transcriptional program that can be identified by the expression of the C-type lectin receptor, CD161. In addition to MAIT cells, it has been demonstrated that a subset of [gamma][delta]T cells expresses CD161 and can be activated by TCR-independent cytokine stimulation. In this study, we sought to clarify the nature of cytokine-responsive human [gamma][delta]T cells. We could link CD161 expression on V[delta]2+ versus V[delta]1+ [gamma][delta]T cells to the observation that V[delta]2+ [gamma][delta]T cells, but not V[delta]1+ [gamma][delta]T cells, robustly produced IFN-[gamma] upon stimulation with a variety of cytokine combinations. Interestingly, both CD161+ and CD161- V[delta]2+ [gamma][delta]T cells responded to these stimuli, with increased functionality within the CD161+ subset. This innate-like responsiveness corresponded to high expression of PLZF and IL-18R[alpha], analogous to MAIT cells. V[delta]2+ [gamma][delta]T cells in human duodenum and liver maintained a CD161+ IL-18R[alpha]+ phenotype and produced IFN-[gamma] in response to IL-12 and IL-18 stimulation. In contrast to MAIT cells, we could not detect IL-17A production but observed higher steady state expression of Granzyme B by V[delta]2+ [gamma][delta]T cells. Finally, we investigated the frequency and functionality of [gamma][delta]T cells in the context of chronic hepatitis C virus infection, as MAIT cells are reduced in frequency in this disease. In contrast, V[delta]2+ [gamma][delta]T cells were maintained in frequency and displayed unimpaired IFN-[gamma] production in response to cytokine stimulation. In sum, human V[delta]2+ [gamma][delta]T cells are a functionally distinct population of cytokine-responsive innate-like T cells that is abundant in blood and tissues with similarities to human MAIT cells.